The main car-buying characteristics of a young generation - Chen, Jiandou; Ibrahim, Rahinah; Azmi, Athira (Asian Scholars Network, 2022)
There is a need to easily see young generation’s characteristics when buying a car in order to increase sales of national cars. This document aims to conduct a systematic literature review synthesis method to evaluate the young generation’s main car-buying characteristics that focus on the youngers self-worth, the youngers personalities and the youngers preferences. Results of the study would include the main car-buying features of the young generation.